Primary Ewing’s sarcoma of vulva: a rare entity and a review of literature - Pal, Anwesa; Mahapatra, Manoranjan; Nayak, Mamita; Nayak, Bhagyalaxmi; Talukder, Anirban; Mohapatra, Janmejaya; Padhy, Ashok; Mahapatra, Tusar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ewing sarcoma family of tumour (ESFT) is a group of bone and soft-tissue neoplasm which has variable neuroectodermal differentiation. In one end Ewing sarcoma (ES) is poorly differentiated, on the other end primitive neuroectodermal tumour (PNET) shows a clear evidence of neural differentiation. Extraosseous Ewing sarcoma (EES) commonly arises in soft tissues of trunk or extremities with a few reported rare sites include oro-naso-laryngo pharynx, neck, pleura, retroperitoneal space, mediastinal space and genital tract. Till now 30 cases of EES of vulva and vagina have been reported in the literature. We report a case of ES vulva in a 35-year-old patient. Her all routine markers were found to be normal, and magnetic resonance imaging (MRI) showed a vulval mass with high vascularity without infiltration to the surrounding structures. Ultrasonography (USG) guided biopsy(histopathology) revealed to be a small round cell tumour with necrosis and clusters of cells around blood vessels. Immunohistochemical staining demonstrated that the cells were positive for membranous CD99 and vimentin with nuclear positivity for NKX2.2, and negative for synaptophysin, chromogranin A, CD 56, Ki 67-30%, whereas all other IHC markers to rule out differentials of small round cell tumour were negative. Based on histopathological examination (HPE) and immunohistochemistry (IHC) panel diagnosis of ES was confirmed. After ruling out for the metastatic lesions,3 cycles of neo adjuvant chemotherapy with VAC were given and planned for surgical resection. After that she is on regular follow up with adjuvant chemotherapy. EES is a rare very rapid growing aggressive tumour requiring IHC, HPE and molecular genetics for exact timely diagnosis and multimodality treatment for better prognosis and survival.